Preparative Chromatography Techniques Applications in Natural Product Isolation - Hostettmann, K Marston, A Hostettmann, M (Springer, 1998)
With the increasing interest in the discovery of new biologically active compounds, there is a constant need to separate complex mixtures effectively, rapidly, and inexpensively. This book aims to provide an idea on how to solve a respective problem and describes, in detail, the apparatus, operation procedures and numerous applications.